New Frontiers in Cementitious and Lime-Based Materials and Composites - Signorini, Cesare; Sola, Antonella; Chakraborty, Sumit; Volpini, Valentina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cement and lime currently are the most common binders in building materials. However, alternative materials and methods are needed to overcome the functional limitations and environmental footprint of conventional products. This Special Issue dedicated to "New frontiers in cementitious and lime-based materials and composites" gathers selected reviews and experimental articles that showcase the most recent trends in this multidisciplinary field. Authoritative contributions from all around the world provide important insights into all areas of research related to cementitious and lime-based materials and composites, spanning from structural engineering to geotechnics, including materials science and processing technology. This Topical Collection is intended to foster innovation and help researchers and developers to identify new solutions for a more sustainable and functional built environment.